2018
DOI: 10.1186/s12870-018-1354-x
|View full text |Cite
|
Sign up to set email alerts
|

Multiple morphogenic culture systems cause loss of resistance to cassava mosaic disease

Abstract: BackgroundMorphogenic culture systems are central to crop improvement programs that utilize transgenic and genome editing technologies. We previously reported that CMD2-type cassava (Manihot esculenta) cultivars lose resistance to cassava mosaic disease (CMD) when passed through somatic embryogenesis. As a result, these plants cannot be developed as products for deployment where CMD is endemic such as sub-Saharan Africa or the Indian sub-continent.ResultIn order to increase understanding of this phenomenon, 21… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 25 publications
1
21
0
Order By: Relevance
“…SSR primer revealed the loss of the resistant gene (319 bp) in callus induced from 2, 4-D media in cultivars agric-rouge and agblehoundo and in callus induced from TDZ medium in agblehoundo. These results concur with those of Beyene et al (2016) and Chauhan et al (2018) who reported the loss of CMD2 resistant gene after regenerating the entire cassava plants. Findings confirm the usefulness of SSR markers in the analysis of conformity of induced calli, similar to works on crops such as caladium tissue culturederived plants by Cao et al (2016).…”
Section: Effect Of Growth Regulators On the Cmd2 Conformity In Of Thesupporting
confidence: 92%
See 1 more Smart Citation
“…SSR primer revealed the loss of the resistant gene (319 bp) in callus induced from 2, 4-D media in cultivars agric-rouge and agblehoundo and in callus induced from TDZ medium in agblehoundo. These results concur with those of Beyene et al (2016) and Chauhan et al (2018) who reported the loss of CMD2 resistant gene after regenerating the entire cassava plants. Findings confirm the usefulness of SSR markers in the analysis of conformity of induced calli, similar to works on crops such as caladium tissue culturederived plants by Cao et al (2016).…”
Section: Effect Of Growth Regulators On the Cmd2 Conformity In Of Thesupporting
confidence: 92%
“…Furthermore, Castro et al (2016) reported in Byrsonima verbascifolia an excellent (100%) callus induction using 2,4-D combined with BAP. Callus-derived somaclonal variation based on morphological and biochemical parameters have been reported by Pajević et al (2004) in sunflower, Jibu et al (2006) in tea, Rajeswari et al (2009) in Sugarcane, Park et al (2010) in Rice, Beyene et al (2016) and Chauhan et al (2018) in cassava. Although, many works have generated cassava plantlets from somatic embryogenesis in different cassava varieties (Anuradha et al, 2015;Atehnkeng et al, 2006;Feitosa et al, 2007;Le et al, 2007;Vidal et al, 2014), there are no reports on such work on cassava varieties in Benin.…”
Section: Introductionmentioning
confidence: 78%
“…However, the plantlets were otherwise phenotypically indistinguishable from the CMD-resistant mother plants from which they were derived. Similarly, Chauhan et al [50] showed that multiple morphogenic culture systems cause loss of resistance to cassava mosaic disease. In their study, they found that 25-36% and 5-10% of regenerated plant lines lost resistance to CMD respectively.…”
Section: Discussionmentioning
confidence: 97%
“…The other CMD resistance alleles (CMD1 and CMD3) are unaffected and still reliable for use. The loss of CMD2-based resistance could provide a method to predict if other traits will share the same phenomenon (Chauhan et al, 2018). There are several potential mechanisms for this effect including somaclonal variation, which (Zamir et al, 1994;Verlaan et al, 2013;Butterbach et al, 2014) Ty-2 NB-LRR class protein S. lycopersicum TYLCV (Yang et al, 2014;Yamaguchi et al, 2018) Ty-4 S. lycopersicum TYLCV (Ji et al, 2009) ty-5 pelota S. lycopersicum TYLCV (Hutton et al, 2012;Scott et al, 2015;Lapidot et al, 2015) Ty-6 S. lycopersicum TYLCV (Scott et al, 2015) CMD1, CMD3 M. esculenta ACMV (Fregene et al, 2000;Akano et al, 2002;Okogbenin et al, 2012) CMD2 M. esculenta ACMV (Akano et al, 2002;Kuria et al, 2017) is caused by epigenetic changes when the cell undergoes the disorganized regeneration phase in tissue culture (Bairu et al, 2011;Lee and Seo, 2018).…”
Section: Naturally Occurring Resistancementioning
confidence: 99%